2016–2017 Arkansas mumps outbreak in a close-knit community: Assessment of the economic impact and response strategies. Issue 6 (5th February 2020) - Pike, Jamison; Marin, Mona; Guo, Angela; Haselow, Dirk; Safi, Haytham; Zhou, Fangjun
Highlights: From August 2016 through July 2017, nearly 3, 000 cases of mumps were reported to ADH. Second largest US mumps outbreak in over 30 years. Over 50% of cases were in the Arkansas Marshallese community, a close-knit community. Costs reflect the response strategies tailored to the affected populations. Total public health response costs were over 2.1 million, approximately 725 per case. Abstract: On August 8, 2016, a confirmed case of mumps was reported to the Arkansas Department of Health (ADH) in an adult resident of Springdale, Arkansas. By July 2017, nearly 3, 000 cases of mumps were reported to ADH from 37 of the 75 counties in Arkansas. Over 50% of cases were in the Arkansas Marshallese community, a close-knit community characterized by large, and extended families sharing the same living space and communal activities. In a statewide effort, ADH collaborated with CDC, the Republic of the Marshall Island's (RMI) Ministry of Health, and the Arkansas Department of Education (ADE) to rapidly respond to and contain the outbreak. We assessed the economic burden to ADH of the outbreak response in terms of containment and vaccination costs, as well as response costs incurred by CDC, RMI, and ADE. The 2016–2017 Arkansas mumps outbreak was the second largest US mumps outbreak in over 30 years and was unique in size, spread, and population affected. Total public health response costs as a result of the outbreak were over 2.1 million, approximately 725 per case. The costs incurred to control this outbreak reflect the response strategies tailored to the affected populations, including consideration of social, cultural, and political factors in controlling transmission and requirements of distinctive strategies for public health outreach. Aside from the burden these outbreaks have on the affected population, we demonstrate the potential for high economic burden of these outbreaks to public health.